Physical and Mechanical Properties of Natural Fiber Polyester Laminate Composites. Issue 1 (November 2021) - Ismadi,; Munawar, S S; Kusumah, S S; Subiyanto, B; Purnomo, D; Akbar, F; Syahrir, A
Abstract: The utilization of natural fibers as reinforcing composites has been widely used. Indonesia has natural fibers abundantly such as ijuk fiber ( Arenga pinnata ), sisal fiber ( Agave Sisalana ) and coconut fiber ( Cocos Nucifera ). Random orientation application of the fiber in composites affected to the lower properties. Therefore, the particular orientation of fibres wereapplied in manufacturing of composite by laminating the short fiber with Polyurethane (PU) adhesive. The size and moisture content (MC) of fiber were 14-15 cm and +10%, respectively. The resin content of PU was 5% by weight of the laminate sheet. The mixture of fibers and PU adhesive was cold pressed for 5 minutes with a thickness of 0.5-1 mm. The laminate sheet of PU-adhesive fibers then mixed with unsaturated polyester resin layer by layer. The fiber laminate composition of composite was varieted such as 1, 2 and 3 layers. The hand layup method was used in the manufacturing of the composite. The physical and mechanical testing like density, moisture content, water absorption, thickness swelling, flexural test (adapt to ASTM D 790 standard) and tensile test (adapt to ASTM D 638 standard) were carried out. In additionmorphological analyses were investigated on composite samples. The results research showed that the net density of polyester, ijuk fiber sheet, sisal fiber sheet, and coconut fiber sheet were 1.21, 0.9, 0.53 and 0.22 g/cm 3 . The range of composite density was 0.99-1.15 g/cm 3 . The single layer composite had lower thickness swelling and water absorption than those of the three layers composite. The highest tensile strength of three layers of sisal fiber composite was higher (33.84 MPa) than that of the three layers of coconut fiber composite (12.04 MPa). The flexural strength of double layers composite from fiber sisal was higher (63.16 MPa) than that of three layers coconut fiber composite (28.65 MPa).